2015
DOI: 10.1177/0956462415586676
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and feasibility of HIV self-testing among men who have sex with men in Peru and Brazil

Abstract: HIV self-testing has the potential to increase testing frequency and uptake. This pilot study assessed the feasibility and acceptability of HIV self-testing in a sample of sexually active men who have sex with men in Peru and Brazil. Participants were trained to use a whole blood rapid HIV self-test and instructed to use the self-test monthly during this three-month study. Test acceptability was measured with self-reported use of the test at the one-month and three-month study visits, and test feasibility was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
100
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(110 citation statements)
references
References 10 publications
9
100
0
1
Order By: Relevance
“…Patient acceptability of self-administered procedures for obtaining biological samples such as urine or vaginal swabs is consistently high [2]. Similarly, acceptability of self-testing for HIV is high in both hypothetical [3-5] and actual-use studies [5-10]. …”
Section: Introductionmentioning
confidence: 99%
“…Patient acceptability of self-administered procedures for obtaining biological samples such as urine or vaginal swabs is consistently high [2]. Similarly, acceptability of self-testing for HIV is high in both hypothetical [3-5] and actual-use studies [5-10]. …”
Section: Introductionmentioning
confidence: 99%
“…Non-RCT projects which have provided participants with a number of HIVSTs with instructions to test frequently have shown that distribution in line with this intervention approach is feasible amongst trans gender women in San Francisco (32), and MSM in Brazil and Peru (21).…”
Section: Reducing Interval Between Infection and Diagnosismentioning
confidence: 99%
“…An internet study among Brazilian MSM found that 47% preferred home-based testing compared with clinic based testing; however, the study did not examine views on the oral test itself 16. In another study examining the acceptability of home-based HIV testing among Brazilian and Peruvian MSM, acceptability of the approach was again high (97%) but oral HIV testing was not one of the options assessed 17. A third study, conducted in Peru among 147 MSM and 45 TGW, focused solely on the hypothetical acceptability of self-testing using the oral HIV test (if free of charge) and reported a high (82%) acceptability 18.…”
Section: Introductionmentioning
confidence: 99%